The Vaginal Metastasis of Ureteral Carcinoma after Left Nephroureterectomy A Case Report - Yamamichi, Gaku (Hinyokika kiyo. Acta urologica Japonica, 2016)
69-year-old woman underwent left nephroureterectomy for left ureteral cancer (urothelial carcinoma (UC), high grade, pT3pN0) in September 2013. She returned to our hospital presenting with asymptomatic macrohematuria in July 2014. Cystoscopy showed tiny papillary tumors in the bladder. We also found genital bleeding from multiple papillary tumors on the vaginal wall. We performed transurethral resection of the bladder tumor and a biopsy of the vaginal wall demonstrated non-invasive UC, high grade. Pelvic magnetic resonance imaging after the operation showed no infiltration outside the bladder wall and vaginal wall. Therefore, we performed endoscopic excision of the vaginal tumor. However we could not resect all vaginal tumors. Irradiation of the vagina and uterus was performed under the diagnosis of metastasis of UC tovagina. Vaginal UC is extremely rare and this is the 26th case report in the literature